PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 131 PEKANBARU - Sony Novita Sari; Hendri Marhadi; Jessi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : The research carried out base on the lowly of the result of math subject in grade 4th SDN 131 Pekanbaru which is about 68,94 within minimal completeness criterion stated is 70. Among 33 student, there was only 15 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on math of the fourth graders in SDN131 Pekanbaru with the application ofproblem based learning. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of contextual teaching and learning model it was abtained student’s outcomes in UH I within average 68,94 basic score 2,03%. The average score form UH II was 78,45 (improved 13,7%). Teachers activities results in the first meeting of the first cycle was 65% (good category), and then 70% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 95% (very good category) and then 100% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 67,5% (fair category), 70% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 95% (veri good category), 100% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of problem based learningmodel can math in fourth graders at SDN 131 PekanbaruKeywords : Problem based learning, Students Achievement the Result Of math Studies.